Regulation of Lung Epithelial Sodium Channels by Cytokines and Chemokines - Wynne, Brandi M.; Zou, Li; Linck, Valerie; Hoover, Robert S.; Ma, He-Ping; Eaton, Douglas C. (Frontiers in Immunology, 2017)
Acute lung injury (ALI) leading to acute respiratory distress (ARDS) is a global health concern. ARDS patients have significant pulmonary inflammation leading to flooding of the pulmonary alveoli. This prevents normal gas exchange with consequent hypoxemia, and causes mortality. A thin fluid layer in the alveoli is normal. The maintenance of this thin layer results from fluid movement out of the pulmonary capillaries into the alveolar interstitium driven by vascular hydrostatic pressure and then through alveolar tight junctions. This is then balanced by fluid reabsorption from the alveolar space mediated by transepithelial salt and water transport through alveolar cells. Reabsorption is a two-step process: first, sodium enters via sodium-permeable channels in the apical membranes of alveolar type 1 and 2 cells followed by active extrusion of sodium into the interstitium by the basolateral Na+, K+-ATPase. Anions follow the cationic charge gradient and water follows the salt-induced osmotic gradient. The proximate cause of alveolar flooding is the result of a failure to reabsorb sufficient salt and water or a failure of the tight junctions to prevent excessive movement of fluid from the interstitium to alveolar lumen. Cytokine- and chemokine-induced inflammation can have a particularly profound effect on lung sodium transport since they can alter both ion channel and barrier function. Cytokines and chemokines affect alveolar amiloride-sensitive epithelial sodium channels (ENaC) which play a crucial role in sodium transport and fluid reabsorption in the lung. This review will discuss the regulation of ENaC via local and systemic cytokines during inflammatory disease and the effect on lung fluid balance.